2014
DOI: 10.3329/akmmcj.v5i2.21131
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of NAT2 Gene and its Association with Prostate Cancer

Abstract: A N acetyltransferases 2 (NAT2) is one of the phase II metabolizing enzyme that participate in the bioconversion of heterocyclic arylamines into electrophilic nitrenium ions, which are important ultimate carcinogens that are directly implicated in tumor initiation process. Prostate epithelial cell express N acetyltransferases (NAT) enzymes and recent molecular epidemiological studies have analyzed the relationship between NAT2 in etiology of prostate cancer. A review by chen (2001) in prostate cancer (PCa) sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Studying polymorphisms in the NAT2 gene is clinically important due to the association identified between polymorphisms in this gene and the development of various socially significant diseases, as well as the sensitivity of individuals to drugs, such as isoniazid, that are used to treat tuberculosis [ 1 , 37 ]. Numerous studies have shown a reliable link between polymorphic variants of NAT genes and the risk of cancer, including cancer of the head and neck, lungs, mammary glands, larynx, bladder, digestive tract [ 38 – 45 ]. The presence of a “slow” NAT2 genotype in combination with a “zero” GSTM1 (0/0) genotype is a risk factor for the development of lymphatic leukemia in children [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studying polymorphisms in the NAT2 gene is clinically important due to the association identified between polymorphisms in this gene and the development of various socially significant diseases, as well as the sensitivity of individuals to drugs, such as isoniazid, that are used to treat tuberculosis [ 1 , 37 ]. Numerous studies have shown a reliable link between polymorphic variants of NAT genes and the risk of cancer, including cancer of the head and neck, lungs, mammary glands, larynx, bladder, digestive tract [ 38 – 45 ]. The presence of a “slow” NAT2 genotype in combination with a “zero” GSTM1 (0/0) genotype is a risk factor for the development of lymphatic leukemia in children [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, over 100 candidate genes for T2DM have been studied in various populations worldwide (Marullo, Gaulton, & Eicher;Zhao et al, 2017). Gene coding for the synthesis of drugs metabolizing enzymes such as NAT2, CYP2R1, CYP3A4, CYP2C9, Glutathione S-transferase has shown to be linked with the susceptibility to Type 2 diabetes mellitus (Al-Shaqha, Alkharfy, Al-Daghri, & Mohammed, 2015;Alexey, 2018;Nesa, Rahman, Kabir, & Rupam, 2014;Rabiee, Marjani, Khajeniazi, & Mojerloo, 2018;Semiz et al, 2011;Wang et al, 2018;Yalin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%